Go Public or Stay Private: A Theory of Entrepreneurial Choice - Arnoud W.A. Boot; Radhakrishnan Gopalan; Anjan V. Thakor (Tinbergen Institute, 2003)
In this paper we analyze an entrepreneur /manager's choice between private and public ownership in a setting in which management needs some elbow room or autonomy to optimally manage the firm. In public capital markets, the corporate governance regime in place exposes the firm to exogenous controls, so that management may lack the autonomy it desires. By contrast, private ownership can provide management the desired autonomy due to the possibility of precisely-calibrated private contracting. The disadvantage of private ownership (relative to public ownership) is that it imposes a cost of illiquidity on those who provide financing. We explore this tradeoff between managerial autonomy and the cast of capital in a simple setting and draw a number of new testable implications.
Keywords: D83; G30; G32; 330; Ownership Structure; Stockmarket Listing; Eigentümerstruktur; Börsengang; Entrepreneurship-Ansatz